Flaxseed Oil Supplementation Improve Gene Expression Levels of PPAR‐γ, LP(a), IL‐1 and TNF‐α in Type 2 Diabetic Patients with Coronary Heart Disease. Issue 11 (15th September 2017) - Hashemzadeh, Ali Akbar; Nasoohi, Nikoo; Raygan, Fariba; Aghadavod, Esmat; Akbari, Elmira; Taghizadeh, Mohsen; Memarzadeh, Mohammad Reza; Asemi, Zatollah
Abstract: This study was carried out to determine the effects of flaxseed oil administration on gene expression levels related to insulin, lipid and inflammation in overweight diabetic patients with coronary heart disease (CHD). This randomized double‐blind, placebo‐controlled trial was conducted among 60 diabetic patients with CHD. Subjects were randomly allocated into two groups to intake either 1000 mg n‐3 fatty acid from flaxseed oil containing 400 mg α‐Linolenic acid [ALA (18:3n‐3)] ( n = 30) or placebo ( n = 30) twice a day for 12 weeks. Gene expression related to insulin, lipid and inflammation were quantified in peripheral blood mononuclear cells (PBMC) of diabetic patients with CHD with RT‐PCR method. Results of RT‐PCR demonstrated that after the 12‐week intervention, compared with the placebo, flaxseed oil supplementation could up‐regulate gene expression of peroxisome proliferator‐activated receptor gamma (PPAR‐γ) ( P = 0.02) in PBMC of diabetic patients with CHD. In addition, compared with the placebo, taking flaxseed oil supplements down‐regulated gene expression levels of lipoprotein(a) [LP(a)] ( P = 0.001), interleukin‐1 (IL‐1) ( P = 0.001) and tumor necrosis factor alpha (TNF‐α) ( P = 0.02) in PBMC of diabetic patients with CHD. We did not observe any significant effect of flaxseed oil supplementation on gene expression levels of low‐density lipoprotein receptor (LDLR), IL‐8 and transforming growth factor beta (TGF‐β) in PBMC of diabetic patients with CHD. Overall, flaxseed oil supplementation for 12 weeks in diabetic patients with CHD significantly improved gene expression levels of PPAR‐γ, LP(a), IL‐1 and TNF‐α, but did not influence LDLR, IL‐8 and TGF‐β.